Controller and Auditor-General v Davison: Three Comments - Hastings, W K (Victoria University of Wellington Law Review, 1996)
This article is a case note of Controller and Auditor-General v Davison CA 226/95, 16 February 1996. The case involved an application for judicial review of an order by the "Winebox" Commission of Inquiry to the Audit Office and KPMG Peat Marwick to produce documents relating to their functions as Government Auditor of the Cook Islands. The three authors make comments about the case and its impact on private international law, noting in particular the doctrine of sovereign immunity. *NOTE: a French version summary is provided at 476.